Retail Chains in Russia: Some Aspects of State Regulation - KARASHCHUK, Oksana; NUSRATULLIN, Ilmir; TRETYAKOV, Vladimir; SHMATOV, Mikhail; REZVAN, Alexander (Journal of Advanced Research in Law and Economics; Vol 10 No 4 (2019): JARLE Vol X Issue 4(42) Summer 2019, 2019)
The objective of this paper is to substantiate some proposals for improving state regulation of the retail network in Russia. In some regions of Russia, there is a lack of retail supply for the population, which requires government support for retail network development. State regulation of the trading network in Russia is carried out via establishing by the authorities of Russia’s administrative regions and local authorities of the minimum standards for public provision of trading floor space. However, only 3% of municipalities in Russia develop these standards; it reflects a low practical significance of the established indicators. The authors made a hypothesis that the indicators of retail floor space per thousand inhabitants, used as standards for the minimum public retail supply in Russia, need to be replaced due to the market development of trade. To test the hypothesis, the papers by authoritative authors on similar issues were studied, which revealed the use of population indicators based on the number of enterprises as a standard in countries with developed markets. A study of the current methodology for standardizing indicators in Russia was also conducted, which showed its insufficient academic rationalizing. According to the results of the study, it was proposed to change the indicator of the minimum public retail supply standard and use the norm of the number of trade organizations per capita, differentiated by the forms of trade. The recommendations of this paper provide the basis for improving the current legal acts on the regulation of norming retail chains in Russia. This study may be interesting for countries with similar conditions for the development of the retail network (a sparsely populated large part of the country, inaccessibility of some settlements, low state stimulation of retail within unprofitable territories).